Development of electronic digital comic learning media based on Gentala Arasy Jambi's ethnomathematics to improve mathematical literacy - Maryono Maryono; Eka Sastrawati; Hendra Budiono (Sriwijaya University Learning and Education International Journal, 2024)
This research was conducted by looking at the educational situation, especially elementary schools because of the lack of teaching variation in the use of digital learning media. The lack of variety in learning media makes students less enthusiastic about participating in learning activities. For this reason, media is needed so that students can see, hear, and read, one of which is comics. The research aims to develop e-comic media containing ethnomathematics, Gental Arasy, and Jambi Province to increase mathematical literacy, foster a spirit of love for the country, and increase student motivation in learning. The development of digital comic research uses Research and Development as well as the 4D development model. The subjects in this research consisted of class V teachers at SDN 214/IV Jambi City and class V students at SDN 214/IV Jambi City. The effectiveness test of e-comic media was analysed using the t-test and N-Gain based on data obtained through motivation questionnaires and creative thinking ability tests given to 12 class V students of SD 214/V Jambi City. The type of data collection carried out is by conducting observations, interviews and questionnaires. The data was analysed using qualitative descriptive and quantitative descriptive analysis techniques. The research results showed that the average expert validity test score was 88%, so it was included in the very valid criteria and product trials on students were 95% in the very good category. Thus, the results of the research concluded that the Gental Arasy Jambi-based comic EDC learning media can increase mathematical literacy in learning.